Analisis Kelayakan Usaha Udang Vaname (Litopenaeus Vannamei) Keramba Jaring Apung Laut di Kepulauan Seribu (Jurnal Agribisnis Indonesia, 2022)
The high demand for vannamei shrimp encourages the government to increase production so that it can compete in the world market, but there is limited capacity in the ponds so that floating net cages of vaname shrimp are cultivated. This new approach requires a feasibility assessment, both economically and socio-ecologically, therefore the aims of this study was to assess it. The research location was determined purposively in the Thousand Islands. Primary data was collected by survey method with interview techniques assisted by structured questions. Secondary data collection is carried out to agencies such as the Center for Coastal and Ocean Resources Studies. The analyzes used are financial analysis and Rapid Appraisal of Fisheries (RAPFISH) analysis. The results show that in the financial aspect, the criteria for B / C ratio are still B / C